An Elective Course on Writing and Publishing a Review Article (Pharmacy Education, 2018)
In effort provide an opportunity for talented and motivated pharmacy students to learn about publishing a scientific review article, Temple University Pharmacy (TUSP) initiated an elective titled "Writing and Publishing a Review Article”. It soon that almost all of the students who enrolled in the elective had the scientific acumen, literature-search skills, and the motivation to go beyond just learning about the process and to actually try to publish a paper. As a result, the course now has as a stated goal the writing and submission of a manuscript to a peer-reviewed journal. Since its inception in 1997, a total of 39 students have taken the course. To date 38 students, working in teams, have had 11 papers published in peer-reviewed journals.